The Asian Menopause Survey: Knowledge, perceptions, hormone treatment and sexual function - Huang, KE; Xu, L; Nasri, N; Jaisamrarn, U (Elsevier Ireland Ltd, 2024)
Objective: To provide current insights into the opinions, attitudes, and knowledge of menopausal women in Asia regarding menopause and hormone replacement therapy (HRT). Study design: Cross-sectional. Main outcome measures: Between January 2006 and February 2006, 1000 postmenopausal women from China, Malaysia, Taiwan, Thailand and Hong Kong were interviewed to determine postmenopausal symptoms, HRT use and knowledge, breast discomfort and knowledge of breast cancer risks; and sexual function. Results: Almost all women reported experiencing postmenopausal symptoms. Sleeplessness (42%) was reported as the main reason for seeking treatment. On average, 54% of women were aware of HRT, despite the fact that most (38%) were unable to mention any associated benefits. Most women had used natural or herbal treatments (37%) for the alleviation of menopausal symptoms. Only 19% had received HRT. 27% of respondents reported having breast discomfort, while 70% reported performing self-breast examinations. 53% of women had never received a mammogram, despite breast cancer concern (50%). 24% of women described HRT as being a risk factor for breast cancer. Most women and their partners reported no reductions in sexual function (66 and 51%, respectively), while 90% of respondents did not seek treatment for reduced sexual function. In the event of sexual dysfunction, 33% of women replied that they would be willing to seek treatment. Conclusions: Many Asian women experience postmenopausal symptoms that are often left untreated (due to the acceptance of menopause as a natural process) or treated with herbal/natural remedies. There was a general lack of knowledge among these women regarding treatment options, HRT, and possible risks associated with HRT. A more concerted effortshould be made to better disseminate information regarding the pathogenesis and risk factors associated with breast cancer, menopause, and menopausal symptoms to Asian women. (C) 2009 Elsevier Ireland Ltd. All rights reserved.